Decriminalization of abortion in Chile. A question of social justice - Donoso Sabando, Claudia (Acta Bioethica, 2016)
The positions on this issue move on a continuum ranging from ultra-conservative to the most liberal movements. In this context establishing health policies based on absolute moral systems doesn't result in political or ethical correctness in pluralistic societies like ours. For this reason, it urges the establishment of minimum agreements that allow the development of happy life projects for every person. Chile, which has a strong anti-abortion policy, needs to review their laws to ensure fair attention to all citizens. The statistics reveal that prohibition does not eliminate the practice of abortions; furthermore, it puts people who are already disadvantaged due to "the social lottery of life" in a worse situation. Paying attention to this issue and acting immediately showing in a tangible way that which has been discussed many times in our country, is a debt of justice that the Chilean state has to all women.